The Risks and Rewards of Speaking Up: Managerial Responses to Employee Voice - Burris, Ethan R. (Academy of Management Journal, 2012)
This article examines whether managerial responses to employees speaking up depend on the type of voice exhibited—that is, whether employees speak up in challenging or supportive ways. In one field study and two experimental studies, I found that managers view employees who engage in more challenging forms of voice as worse performers and endorse their ideas less than those who engage in supportive forms of voice. Further, perceptions of loyalty and threat mediated these relationships, but in different ways. I discuss implications for research on voice, proactivity, and social persuasion.